PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM - Alfian Bagas Wiratama; Eny Kusumawati (Prosiding University Research Colloquium, 2021)
This study aims to analyze the effect of dividend policy, sales growth,company size, and good corporate governance on stock prices. Goodcorporate governance used is managerial ownership andindependent board of commissioners. The population of this researchis companies that are consistently included in the LQ-45 Index on theIndonesia Stock Exchange (IDX) during the 2015-2019 period. Thenumber of samples taken was 115 data with 23 companies selectedper year using purposive sampling technique. Data collection wascarried out using documentary methods on secondary data. Theanalysis technique used is multiple linear regression analysis withthe help of the SPSS 20 computer program. The results show thatcollectively, dividend policy, sales growth, company size, managerialownership, and independent board of commissioners have asignificant effect on stock prices. Partially, managerial ownershiphas a significant effect on stock prices, while dividend policy, salesgrowth, company size, and independent board of commissioners haveno significant effect on stock prices.